Method for Assessing Implementation of Design Build Project Delivery System in Indonesian Road Infrastructure Projects (Cases Study : Balai Besar Pelaksanaan Jalan Nasional V) - Ashri Maharani; Hitapriya Suprayitno; Herry Budianto (Institut Teknologi Sepuluh Nopember, 2015)
Public infrastructure, particularly road infrastructure, has a strong linkage with the economic growth of a nation. Management of road infrastructure by the DG of Highways-Ministry for PW is currently implemented by using traditional methods of DBB contract system. Although DBB approach is considered more fair for the contractor, it may not be able to create more value for the Government. Long periods of procurement, often result in undesirable outcomes such as excessive cost, unsatisfactory quality and delays in implementation time. The DB project delivery system is expected to answer the above problem and therefore, there is a need to examine how to assess the feasibility of DB Contract implementation for road infrastructure projects under the authority of BBPJN V. This paper present the method assessment development